Preparation method of high-quality and large-size bulk-phase tin triphosphide single crystal

Through the premixer mixing, molten salt method and muffle furnace tube sealing sintering method, the heating rate and temperature are controlled, and high-purity and large-size bulk tin triphosphide single crystals are successfully prepared, solving the problems of low purity and small grain size of tin triphosphide materials in the prior art, and achieving efficient preparation of tin triphosphide crystals.

CN119913600AActive Publication Date: 2025-05-02QUFU NORMAL UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510139628.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-08
Publication Date
2025-05-02
Estimated Expiration
2045-02-08

AI Technical Summary

Technical Problem

In the prior art, the tin triphosphide material has low purity and small grain size, making it difficult to prepare high-quality, large-size bulk tin triphosphide single crystals.

Method used

The premixer mixing, molten salt method, and muffle furnace tube sealing sintering method are used to control the temperature rise rate to 3℃/min and the temperature is 300-500℃. Through these steps, high-quality, large-size bulk tin triphosphide materials are successfully prepared.

Benefits of technology

The preparation of high-purity and large-size tin triphosphine single crystals has been achieved, with a crystal size of up to 178.43μm, which is suitable for subsequent physical properties of tin triphosphine crystals. Compared with traditional methods, the production cycle is short, the crystal size is large, and the crystal purity is high.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119913600A_ABST
    Figure CN119913600A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a high-quality and large-size bulk-phase tin triphosphide single crystal, and belongs to the technical field of preparation of tin triphosphide single crystals. The preparation method comprises the following steps: (1) mixing tin powder and red phosphorus powder according to a molar ratio of 1: 4, and adding potassium chloride and aluminum chloride according to a certain ratio; (2) the raw materials in the step (1) are put into a quartz tube for vacuum tube sealing, the vacuum degree in the quartz tube is 2 * 10 <-2 > Pa or below, and the raw materials are evenly mixed through a premixing machine; (3) sintering the quartz tube subjected to vacuum tube sealing in the step (2), setting the sintering temperature to be 300-500 DEG C, keeping the temperature for 48-92 hours, and raising the temperature rate to be 3 DEG C / min; and (4) cooling the quartz tube sintered in the step (3) to room temperature, and cleaning a sample to obtain the tin triphosphide single crystal. According to the preparation method, the preparation of the high-quality micron-level layered tin triphosphide single crystal can be ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention discloses a method for preparing high-quality, large-sized bulk tin phosphide single crystals, and belongs to the technical field of new energy materials. In particular, it relates to a method for preparing high-quality, large-sized bulk tin phosphide single crystals and micrometer-level layered tin phosphide single crystals prepared by the preparation method. Background Art

[0002] Tin phosphide has a similar crystal structure to rhombohedral black phosphorus and exhibits metallic conductivity, which is much higher than that of black phosphorus. The stripping energy of a single layer of tin phosphide is 0.45 J m -2 , and the peeling energy of black phosphorus (0.36 J m -2 ) are not much different, indicating that tin phosphide is easy to dissociate. Monolayer tin phosphide has an ultra-low sodium ion migration barrier (0.03eV), which is lower than that of monolayer black phosphorus (0.08V), which means that monolayer tin phosphide will have high ion mobility when used as an electrode material. At present, the preparation methods of tin phosphide materials are mainly gas phase method and ball milling method. Among them, the tin phosphide material prepared by gas phase method will have 3% Sn3P4, while the tin phosphide grains prepared by ball milling method are nanometer-scale and the crystal quality is poor. Summary of the invention

[0003] In view of this, in order to solve the technical problems of low purity and small grain size of the currently prepared bulk tin phosphide materials. On the one hand, the present invention provides a method for preparing high-quality, large-sized bulk tin phosphide single crystals, which successfully prepares high-quality, large-sized bulk tin phosphide materials through premixing, molten salt method, muffle furnace sealed tube sintering method, and controlling the heating rate at 3°C / min and the temperature at 300-500°C, and can ensure the preparation of micron-level layered tin phosphide single crystals.

[0004] To achieve the above object, the present invention provides the following technical solutions:

[0005] A method for preparing high-quality, large-size bulk tin phosphide single crystals comprises the following steps:

[0006] Step (1), mixing tin powder and red phosphorus powder in a molar ratio of 1:4, and adding a certain proportion of potassium chloride and aluminum chloride;

[0007] Step (2), placing the raw materials of step (1) into a quartz tube, sealing the tube under vacuum, and mixing the raw materials uniformly with a premixer;

[0008] Step (3), sintering the quartz tube after vacuum sealing in step (2), setting the sintering temperature to 300-500° C. for 48-92 hours, and the heating rate to 3° C. / min;

[0009] Step (4), cooling the quartz tube after sintering in step (3) to room temperature, washing the sample, and obtaining a tin triphosphide single crystal.

[0010] Preferably, in step (1), the molar ratio of tin powder, red phosphorus powder, potassium chloride and aluminum chloride is 1:4:(3.5-7):(1.75-3.5).

[0011] Preferably, in step (2), the premixer mixes the materials for 30-60 minutes.

[0012] Preferably, in step (2), the quartz tube needs to be vacuum sealed in a glove box.

[0013] Preferably, the water oxygen value is below 0.1 ppm.

[0014] Preferably, in step (2), the vacuum degree of the quartz tube for vacuum sealing is 2*10 -2 Below Pa.

[0015] Preferably, in step (4), the cleaning operation is ultrasonic treatment.

[0016] Preferably, the ultrasonic treatment conditions are: ultrasonic power 100 W, ultrasonic time 30-60 min.

[0017] Preferably, in step (1), the tin powder and red phosphorus powder are tin powder and red phosphorus powder that have not been specially treated.

[0018] On the other hand, the present invention also provides a high-quality, large-size bulk tin phosphide single crystal, which is prepared by the above-mentioned method for preparing high-quality, large-size bulk tin phosphide single crystal, and the tin phosphide single crystal is of high quality and micron level.

[0019] The method for preparing high-quality, large-sized bulk tin phosphide single crystals provided by the present invention successfully prepares high-quality, large-sized bulk tin phosphide materials by mixing, molten salt method, muffle furnace sealed tube sintering method, and controlling the heating rate to 3°C / min and the temperature to 300-500°C. Compared with the prior art, the method has the following beneficial effects:

[0020] (1) The present invention overcomes the technical defect that it is difficult to prepare high-purity, large-size tin phosphide single crystals, and realizes the preparation of high-purity tin phosphide single crystals with a crystal size of up to 178.43 μm, providing raw materials for subsequent research on the physical properties of tin phosphide crystals.

[0021] (2) The present invention adopts molten salt sintering technology to prepare tin phosphide single crystals. Compared with the traditional gas phase method and ball milling method, it has a short production cycle, large crystal size and high crystal purity.

[0022] (3) This method can be used to prepare tin phosphide crystals in large quantities. By expanding the size of the quartz tube, the preparation of gram-level tin phosphide crystals can be achieved at one time, which is of great significance for the subsequent research on tin phosphide crystals.

[0023] (4) The high-quality, large-sized tin phosphide crystals prepared by the molten salt method of the present invention can be used as a precursor for the preparation of two-dimensional tin phosphide crystals, and can ensure the preparation of micrometer-level two-dimensional tin phosphide crystals. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 is the XRD pattern of the bulk tin phosphide sample obtained in Example 1;

[0025] Figure 2 This is the Raman image of the bulk tin phosphide sample obtained in Example 1;

[0026] Figure 3 is a scanning electron microscope image of the bulk tin triphosphide sample obtained in Example 1, and a and b are scanning electron microscope images of the bulk tin triphosphide sample at different magnifications, respectively;

[0027] Figure 4 This is a scanning electron microscope energy spectrum of the bulk tin triphosphide sample obtained in Example 1. Figure 4 In the figure, a is a scanning electron microscope image, b is an enlarged image of the specified area in a, and ce is an energy dispersive X-ray spectrum (EDX) image of the specified area in a;

[0028] Figure 5 XRD diagrams of bulk tin phosphide samples obtained in Examples 1-4 and Comparative Examples 1-2;

[0029] Figure 6 This is a scanning electron microscope image of the bulk tin triphosphide sample obtained in Example 2;

[0030] Figure 7 This is a scanning electron microscope image of the bulk tin phosphide sample obtained in Comparative Example 2;

[0031] Figure 8 This is a scanning electron microscope image of the bulk tin triphosphide sample obtained in Comparative Example 3;

[0032] Fig. 9 This is a scanning electron microscope image of the bulk tin triphosphide sample obtained in Comparative Example 4. DETAILED DESCRIPTION

[0033] The present invention provides a method for preparing a high-quality, large-size bulk tin phosphide single crystal, comprising the following steps:

[0034] Step (1), tin powder and red phosphorus powder are mixed in a molar ratio of 1:4, and a certain proportion of potassium chloride and aluminum chloride are added. If the molar ratio of tin powder and red phosphorus powder during the sealed tube sintering process is lower than 1:4, Sn4P3 impurities will appear in the single crystals obtained from the sealed tube; if the molar ratio of tin powder and red phosphorus powder is higher than 1:4, black phosphorus impurities will appear in the subsequent high-temperature sintering process; therefore, in order to prepare high-purity tin triphosphide crystals, the molar ratio of tin powder and red phosphorus powder is set to 1:4.

[0035] Potassium chloride and aluminum chloride are used as co-solvents. Tin powder and red phosphorus powder are preferably tin powder and red phosphorus powder that have not been specially treated. Among them, "not specially treated" means that the purchased raw materials are used without further purification. The molar ratio of tin powder, red phosphorus powder, potassium chloride and aluminum chloride is preferably 1:4:(3.5-7):(1.75-3.5), and more preferably 1:4:3.5:1.75.

[0036] Step (2), the raw materials of step (1) are placed in a quartz tube and sealed under vacuum, and the raw materials are mixed evenly with a premixer. Preferably, the premixer is used to mix the raw materials for 30-60 minutes. Before the quartz tube is sealed under vacuum, the sample needs to be loaded in a glove box, and the water oxygen value is preferably less than 0.1ppm. Preferably, in step (2), the vacuum degree of the quartz tube for vacuum sealing is 2*10 -2 Pa or less, that is, the vacuum degree is 2*10 -2 Anything below Pa is acceptable.

[0037] Step (3), sintering the quartz tube after vacuum sealing in step (2), setting the sintering temperature to 300-500°C for 48-92h, and heating rate to 3°C / min. In the muffle furnace sintering step, the heating rate and sintering temperature are key factors affecting the purity and grain size of bulk tin phosphide; the heating rate is controlled at 3°C / min to ensure that the optimal temperature for obtaining high-purity, large-size tin phosphide is 400°C; as the temperature increases, tin phosphide decomposes into black phosphorus and Sn4P3, while when the temperature decreases, the tin phosphide grains cannot grow.

[0038] Step (4), cooling the quartz tube after sintering in step (3) to room temperature, washing the sample, and obtaining a tin triphosphide single crystal. The washing operation is ultrasonic treatment, specifically: placing the sample in deionized water for ultrasonic treatment, with an ultrasonic power of 100 W and an ultrasonic time of 30 min to remove chloride, and obtaining a tin triphosphide single crystal.

[0039] The technical solution of the present invention is described clearly and in detail below in conjunction with specific embodiments.

[0040] If no specific techniques or conditions are specified in the examples, the products were followed. If no manufacturer is specified for the reagents or instruments used, they are all commercially available conventional products.

[0041] Example 1

[0042] (1) Tin powder and red phosphorus powder are used as raw materials, and the water oxygen value in the glove box is 0.05 ppm. The molar ratio of tin powder to red phosphorus powder is selected to be 1:4, and potassium chloride and aluminum chloride are added in a molar ratio of 3.5:1.75 as co-solvents.

[0043] (2) The mixed powder was placed in a quartz tube with a diameter of 8 mm; the raw materials were mixed evenly using a premixer for 45 min, and a vacuum tube sealer was used to seal the raw materials until the vacuum degree reached 2*10 -2 Pa or less, and seal the quartz tube.

[0044] (3) The quartz tube is placed in a muffle furnace and the sintering temperature is set to 400°C for 92 h with a heating rate of 3°C / min.

[0045] (4) After sintering, wait for the quartz tube to cool to room temperature, place the sample in deionized water for ultrasonic treatment, with an ultrasonic power of 100 W and an ultrasonic time of 30 min to remove chloride, and vacuum dry for 12 h to obtain a tin phosphide single crystal.

[0046] Example 2

[0047] Same as Example 1, except that in step (3), the insulation time is 48 hours.

[0048] Example 3

[0049] Same as Example 1, except that in step (3), the sintering temperature is 500°C.

[0050] Example 4

[0051] Same as Example 1, except that in step (3), the sintering temperature is 300°C.

[0052] Example 5

[0053] Same as Example 1, except that in step (1), potassium chloride and aluminum chloride are added in a molar ratio of 7:3.5.

[0054] Example 6

[0055] Same as Example 1, except that in step (1), potassium chloride and aluminum chloride are added in a molar ratio of 5:2.5.

[0056] Comparative Example 1

[0057] The same as Example 1, except that in step (1), potassium chloride and cesium chloride are selected as the co-solvents.

[0058] Comparative Example 2

[0059] The same as Example 1, except that in step (1), the raw materials are tin powder and red phosphorus powder in a molar ratio of 1:3, and no co-solvent is added. The synthesis method of Comparative Example 2 is a conventional synthesis method in the prior art.

[0060] Comparative Example 3

[0061] Same as Example 1, except that in step (3), the heating rate is 5°C / min.

[0062] Comparative Example 4

[0063] Same as Example 1, except that in step (3), the heating rate is 1°C / min.

[0064] Figure 1 This is the XRD pattern of the bulk tin phosphide sample in Example 1. By comparing it with the standard PDF card, the successful preparation of high-purity tin phosphide is proved. Figure 2 The Raman spectrum of the bulk tin phosphide sample in Example 1 shows the dominant phase of tin phosphide, showing the positions at 139, 246, 323, and 393 cm -1 The four bands can correspond to feature A respectively. 1 g、B 2g , B 3g and A 2 g Vibration mode. Figure 3 These are scanning electron microscope images of the bulk tin phosphide sample in Example 1 at different magnifications, where a and b are scanning electron microscope images of the bulk tin phosphide sample at different magnifications, respectively. A clear layered structure can be seen from a and b, and the largest tin phosphide flake is as high as 178.43 microns, which is much larger than the hundred-nanometer-level tin phosphide particles prepared by the ball milling method. Figure 4 a is a scanning electron microscope image of the bulk tin phosphide sample, b is a scanning electron microscope image of the bulk tin phosphide sample at a magnified multiple, c shows the energy dispersive x-ray spectrum (EDX), d and e are elemental mapping images, showing that Sn and P elements are evenly distributed with an atomic ratio of ~1:3, which is close to the ideal stoichiometric ratio. Figure 5 The XRD diagrams of bulk tin phosphide samples in Examples 1-4 and Comparative Examples 1-2 show that Example 1 synthesizes high-quality, high-purity tin phosphide crystals. Example 2 can synthesize tin phosphide because of the short holding time, but the grains are relatively small. Example 3: When the sintering temperature is 500°C, mixed phases of Sn4P3 and black phosphorus will appear; Example 4: When the sintering temperature is 300°C, mixed phases of Sn4P3 and black phosphorus will also appear; Comparative Example 1: When the co-solvents are potassium chloride and cesium chloride, tin phosphide cannot be synthesized, and mixed phases of Sn4P3 and black phosphorus will appear. Comparative Example 2: When no co-solvent is added, tin phosphide can be synthesized, but the grains are only a few microns in size. Figure 6 This is a scanning electron microscope image of the bulk tin phosphide sample obtained in Example 2. It can be seen from the image that due to the short holding time, the grains are relatively small, and as the holding time increases, the grains grow larger. Figure 7 This is a scanning electron microscope image of the bulk tin phosphide sample obtained in Comparative Example 2. Figure 7 It can be clearly seen that without adding a solvent, the grains are only a few microns. Figure 8 , 9 The scanning electron microscope images of the bulk tin phosphide samples obtained in comparative example 3 and comparative example 4 respectively show the influence of different heating rates on the grain size. A heating rate that is too fast or too slow is not conducive to grain growth.

[0065] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing high-quality, large-size bulk tin phosphide single crystals, characterized in that: The steps include: Step (1), mixing tin powder and red phosphorus powder in a molar ratio of 1:4, and adding a certain proportion of potassium chloride and aluminum chloride; Step (2), placing the raw materials of step (1) into a quartz tube, sealing the tube under vacuum, and mixing the raw materials uniformly with a premixer; Step (3), sintering the quartz tube after vacuum sealing in step (2), setting the sintering temperature to 300-500° C. for 48-92 hours, and the heating rate to 3° C. / min; Step (4), cooling the quartz tube after sintering in step (3) to room temperature, washing the sample, and obtaining a tin triphosphide single crystal.

2. The method for preparing a high-quality, large-size bulk tin phosphide single crystal according to claim 1, characterized in that: In step (1), the molar ratio of tin powder, red phosphorus powder, potassium chloride and aluminum chloride is 1:4:(3.5-7):(1.75-3.5).

3. The method for preparing a high-quality, large-size bulk tin phosphide single crystal according to claim 1, characterized in that: In step (2), the premixer mixes the materials for 30-60 minutes.

4. The method for preparing a high-quality, large-size bulk tin phosphide single crystal according to claim 1, characterized in that: In step (2), the process needs to be carried out in a glove box before the quartz tube is vacuum sealed.

5. The method for preparing a high-quality, large-size bulk tin phosphide single crystal according to claim 4, characterized in that: The water oxygen value is less than 0.1ppm.

6. The method for preparing a high-quality, large-size bulk tin phosphide single crystal according to claim 1, characterized in that: In step (2), the vacuum degree of the quartz tube for vacuum sealing is 2*10 -2 Below Pa.

7. The method for preparing a high-quality, large-size bulk tin phosphide single crystal according to claim 1, characterized in that: In step (4), the cleaning operation is ultrasonic treatment.

8. The method for preparing a high-quality, large-size bulk tin phosphide single crystal according to claim 7, characterized in that: The ultrasonic treatment conditions are as follows: ultrasonic power 100 W, ultrasonic time 30-60 min.

9. A method for preparing high-quality, large-size bulk tin phosphide single crystals according to any one of claims 1 to 8, characterized in that: In step (1), the tin powder and the red phosphorus powder are tin powder and red phosphorus powder that have not been specially treated.

10. A high-quality, large-size bulk tin phosphide single crystal, characterized in that: The high-quality, large-size bulk tin phosphide single crystal is prepared by the preparation method of any one of claims 1 to 9, wherein the tin phosphide single crystal is a micron-level layered tin phosphide single crystal.

Citation Information

Patent Citations

  • Preparation method of large-dimension granular tin phosphide compound

    CN109534308A

  • Tin disulfide-black phosphorus composite material as well as preparation method and application thereof

    CN111252806A

  • Method for producing Sn-containing sulfide-based solid electrolyte

    CN115023773A

  • Two-dimensional tin triphosphide nanosheet as well as preparation method and application thereof

    CN117486177A

  • Method for production of groups iii-v compound crystal

    JP2011026176A